Large adrenal cyst masquerading as a pancreatic cystic tumor: a rare diagnosis based on endoscopic ultrasound - Voudoukis, Evangelos; Velegraki, Magdalini; Khamaysi, Iyad; Karoumpalis, Ioannis; Kazamias, Georgios; Fragaki, Maria; Mastorakis, Emmanouil; Paspatis, Gregorios (Endoscopy International Open, 2018)
Adrenal cystic lesions constitute a rare finding and usually are diagnosed incidentally as retroperitoneal cysts during imaging studies. A major issue, especially for the large-sized ones, is their preoperative diagnosis and management, as imaging modalities often fail to detect their exact origin prior to surgery. We report a case of a big adrenal cyst that was mistakenly diagnosed and followed up as pancreatic cystic tail tumor. Our thorough workup, which included endoscopic ultrasound (EUS), managed to delineate an adrenal gland-originated cyst and altered further management of the patient. According to our knowledge, this is the first report in literature in which EUS proved its superiority over other imaging studies in clarifying the origin of an ambiguous big retroperitoneal cyst. We believe that for cases of large retroperitoneal cystic lesions, EUS consists the optimal diagnostic and sampling tool.